Hubungan pengetahuan gizi, konsumsi makanan cepat saji, asupan zat gizi makro, dan aktivitas fisik dengan status gizi pada remaja : English - Tiyas Ayu; Anna Fitriani; Rahmatika Nur Aini (ARGIPA (Arsip Gizi dan Pangan), 2022)
Nutritional status, a description of consumption for a long time, can be in the form of undernutrition status, normal nutrition status, or overnutrition status. Many factors can influence adolescent nutritional status, including eating-sleep habits that contribute to an energy imbalance between calorie intake and energy expenditure, physical activity and inactive behavior, energy, macronutrient intake, frequency of fast food, genetics, intake, and body image. The purpose of this study was to see the relationship between balanced nutrition knowledge, frequency of fast food consumption, energy intake, protein, fat, carbohydrates, and physical activity with nutritional status in adolescents. The study was conducted in the region RW 05 Bintaro, South Jakarta in July - August 2020. The methodology used quantitative and cross-sectional. Data in this study was secondary data and primary data with the sampling technique, namely purposive sampling. The analysis technique used the fisher exact test and spearman correlation. The results of the study showed no significant relationship between nutritional knowledge, energy, macronutrient intake, and physical activity with nutritional status and there is no correlation between the frequency of fast food consumption and nutritional status.